FitKids360: Design, Conduct, and Outcomes of a Stage 2 Pediatric Obesity Program. (20th August 2014) - Tucker, Jared M.; Eisenmann, Joey C.; Howard, Kathleen; Guseman, Emily H.; Yee, Kimbo E.; DeLaFuente, Kimberly; Graybill, Jill; Roberts, Meggie; Murphy, Megan; Saturley, Heather; Peterson, Tom
Abstract : This paper describes FitKids360, a stage 2 pediatric weight management program. FitKids360 is a physician-referred, multicomponent, low-cost healthy lifestyle program for overweight and obese youth 5–16 years of age and their families. FitKids360 provides an evidence-based approach to the treatment of pediatric overweight by targeting patients' physical activity, screen time, and dietary behaviors using a family-centered approach. The intervention begins with a two-hour orientation and assessment period followed by six weekly sessions. Assessments include lifestyle behaviors, anthropometry, and the Family Nutrition and Physical Activity (FNPA) survey, which screens for obesogenic risk factors in the home environment. Outcomes are presented from 258 patients who completed one of 33 FitKids360 classes. After completing FitKids360, patients increased moderate to vigorous physical activity by 14 minutes (P = 0.019 ), reduced screen time by 44 minutes (P < 0.001 ), and improved key dietary behaviors. Overall, FNPA scores increased by 9% (P < 0.001 ) and 69% of patients with "high risk" FNPA scores at baseline dropped below the "high risk" range by followup. Patients also lowered BMIs (P = 0.011 ) and age- and sex-adjusted BMIz -scores (P < 0.001 ) after completing the 7-week program. We hope this report will be useful to medical and public health professionals seeking to develop stage 2 pediatric obesity programs.